2024
DOI: 10.1002/prp2.1171
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in obesity: Mechanisms and advances in therapies based on natural products

Peng Chen,
Yulai Wang,
Fuchao Chen
et al.

Abstract: Obesity is a major risk factor for morbidity and mortality because it has a close relationship to metabolic illnesses, such as diabetes, cardiovascular diseases, and some types of cancer. With no drugs available, the mainstay of obesity management remains lifestyle changes with exercise and dietary modifications. In light of the tremendous disease burden and unmet therapeutics, fresh perspectives on pathophysiology and drug discovery are needed. The development of epigenetics provides a compelling justificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 152 publications
1
0
0
Order By: Relevance
“…A clinical trial of genistein alone has been reported to have a beneficial effect on postmenopausal females with metabolic syndrome [230]. Relevant to the present discussion are also reports that flavonoids, including genistein, can exert epigenetic effects [231][232][233][234][235]. Therefore, several aspects of these diets and natural products are very compatible with the proposed epigenetic-based mechanism for post-menopausal conditions.…”
Section: Conclusion and The Way Forwardsupporting
confidence: 59%
“…A clinical trial of genistein alone has been reported to have a beneficial effect on postmenopausal females with metabolic syndrome [230]. Relevant to the present discussion are also reports that flavonoids, including genistein, can exert epigenetic effects [231][232][233][234][235]. Therefore, several aspects of these diets and natural products are very compatible with the proposed epigenetic-based mechanism for post-menopausal conditions.…”
Section: Conclusion and The Way Forwardsupporting
confidence: 59%